2015
DOI: 10.1007/s11011-015-9757-y
|View full text |Cite
|
Sign up to set email alerts
|

Behavioural and biochemical changes in maternally separated Sprague–Dawley rats exposed to restraint stress

Abstract: Early life adversity has been associated with the development of various neuropsychiatric disorders in adulthood such as depression and anxiety. The aim of this study was to determine if stress during adulthood can exaggerate the depression-/anxiety-like behaviour observed in the widely accepted maternally separated (MS) Sprague-Dawley (SD) rat model of depression. A further aim was to determine whether the behavioural changes were accompanied by changes in hippocampal brain-derived neurotrophic factor (BDNF) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
15
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 90 publications
3
15
0
Order By: Relevance
“…In agreement with previous studies [25,27,68], the present study showed that SIR has no effect on coping strategy in the FST. Furthermore, the behavioral scores of MS180 rats in the FST apparently were not adversely affected by SIR.…”
Section: Discussionsupporting
confidence: 94%
“…In agreement with previous studies [25,27,68], the present study showed that SIR has no effect on coping strategy in the FST. Furthermore, the behavioral scores of MS180 rats in the FST apparently were not adversely affected by SIR.…”
Section: Discussionsupporting
confidence: 94%
“…RS in mice subjected to MS did not induce a higher level of depressive behavior, indicating that RS and MS may share a similar pathway for inducing depression-like behaviors. Similar results were found in the rats that RS did not enhance the MS effect on depression (van Zyl et al, 2016).…”
Section: Some Work Indicated That Additional Stress In Adolescence Orsupporting
confidence: 87%
“…In the open field, total distance and distance traveled next to the walls was higher in juvenile MS than in NH juvenile male rats (PND-40 -45), suggesting increased locomotion, as reported (37); this or other variables were no different in male adults, nor in female rats at either age (Table 1).…”
Section: Effect Of Ms On Behavior Of Juvenile and Adult Ratssupporting
confidence: 58%